2022
DOI: 10.1111/csp2.12813
|View full text |Cite
|
Sign up to set email alerts
|

Forgotten forbs: Standard vegetation surveys underrepresent ecologically and culturally important forbs in a threatened grassland ecosystem

Abstract: Forbs are a culturally and ecologically important yet poorly studied component of the Pacific Northwest Bunchgrass (PNB) ecosystem of western North America. Because many PNB forbs emerge early in the spring and senesce at the onset of summer, typical vegetation surveys, which occur mid-summer, likely underrepresent forbs. We evaluated how the timing of vegetation sampling affected estimates of perennial forb abundance, richness, and floral density, with a focus on species that are culturally significant to Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Our results showed that the species composition of blooming plant and bee communities varied widely through the growing season. Peaks in species richness occurred relatively early in both systems (before or during June), a result consistent with previous work in the western United States (Golet et al 2011; Kimoto et al 2012a, 2012b; Rhoades et al 2018; Endress et al 2022). In addition, peaks in bee and blooming forb richness occurred at generally the same time in both systems, a pattern also observed elsewhere (Potts et al 2003; Ebeling et al 2008; Holzschuh et al 2012).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results showed that the species composition of blooming plant and bee communities varied widely through the growing season. Peaks in species richness occurred relatively early in both systems (before or during June), a result consistent with previous work in the western United States (Golet et al 2011; Kimoto et al 2012a, 2012b; Rhoades et al 2018; Endress et al 2022). In addition, peaks in bee and blooming forb richness occurred at generally the same time in both systems, a pattern also observed elsewhere (Potts et al 2003; Ebeling et al 2008; Holzschuh et al 2012).…”
Section: Discussionsupporting
confidence: 90%
“…In other instances, range managers could leverage herders employed for other purposes (e.g., as predator deterrents) to monitor and move stock animals to targeted, less sensitive habitats until plant blooms in more sensitive areas have begun to senesce ( Barnes 2015 ;Stephenson et al 2016 ). Two added benefits of delayed-onset grazing in native bunchgrass prairie are 1) native bunchgrasses are less sensitive to overgrazing later in the year ( Schroeder and Johnson 2019 ) and 2) many culturally important forbs are earlyemerging plants or blooms harvested in spring or early summer, which senesce later in the season ( Endress et al 2022 ). Both benefits suggest that phenologically targeted grazing can benefit more than just bees and flowering plants.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, our findings echo those of others in illustrating potential trade-offs of indaziflam between releasing (or at least not damaging) established, long-lived natives that make up the bulk of biomass in perennial ecosystems (Seshadri and Hardin 2018; Clark et al 2019, 2020; Arathi and Hardin 2021) and potentially losing diversity held in the short-lived native species pool (Meyer-Morey et al 2021; Courkamp et al 2022b), or even long-lived plants that are not well established (Terry et al 2021) or are held in the shallow seed bank (Meyer-Morey et al 2021). While perennial grasses have historically been the focus of grassland and rangeland studies due to their importance as forage, short-lived forbs also fill critical roles (Pokorny et al 2004; Meyer-Morey et al 2021; Endress et al 2022). In particular, many forbs have spring phenologies, providing important early-season wildlife forage (Willms and McLean 1978; Marshal et al 2004; Navarro et al 2023), as well as exploiting the same resource niches as winter annual grasses (Leger et al 2014), potentially providing a degree of biotic resistance (Herron et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…An additional benefit of remotely sensed imagery is the capacity for flexible deployment and image acquisition, in response to disturbance and phenological events (Bogdan et al 2021; Gonzales et al 2022). For arid or semi‐arid systems where plants are only visible for brief phenological windows, field surveys may underrepresent counts of crucial functional groups (Endress et al 2022). An alternative approach to our workflow that could potentially reduce the technical costs of segmentation and crown‐to‐crown matching would be to produce data products that represent aggregate cover and count metrics, rather than survival and growth of individuals.…”
Section: Discussionmentioning
confidence: 99%